Simiao Wan and its ingredients alleviate type 2 diabetes mellitus via IRS1/AKT2/FOXO1/GLUT2 signaling - Xia, Ting; Xu, Wen-Jie; Hu, Yan-Nan; Luo, Zhen-Ye; He, Wen; Liu, Chang-Shun; Tan, Xiao-Mei (Frontiers in Nutrition, 2023)
Background: Type 2 diabetes mellitus (T2DM) is a metabolic disease. Simiao Wan (SMW) is a commonly used clinical drug for hyperuricemia treatment. SMW has been confirmed to improve insulin resistance and is expected to be a novel hypoglycemic agent. However, the hypoglycemic bioactive ingredients and mechanisms of action of SMW are unclear. Objective: To explore the hypoglycemic effects and reveal the mechanisms of SMW and main bioactive ingredients (SMW-BI). Study design and methods: The hypoglycemic effects of SMW and SMW-BI were verified in a mouse model of T2DM induced by streptozotocin and a high-fat and high-sugar diet. Network pharmacology was used to predict the mechanisms of SMW and SMW-BI. Histological analysis and real-time quantitative PCR (RT-qPCR) verified network pharmacology results. RT-qPCR results were further verified by immunofluorescence and molecular docking. The correlation between proteins and biochemical indicators was analyzed by Spearman’s correlation. Results: Chlorogenic acid, phellodendrine, magnoflorine, jateorhizine, palmatine, berberine, and atractydin were identified as SMW-BI. After eight weeks of treatment, SMW and SMW-BI decreased the levels of fasting blood glucose, total cholesterol, triacylglycerols, and low-density lipoprotein cholesterol, increased the level of high-density lipoprotein cholesterol, alleviated weight loss, and increased serum insulin levels in T2DM mice. In addition, SMW and SMW-BI improved hepatocyte morphology in T2DM mice, decreased the number of adipocytes, and increased liver glycogen. Network pharmacological analysis indicated that SMW and SMW-BI may exert hypoglycemic by regulating IRS1/AKT2/FOXO1/GLUT2 signaling. Moreover, correlation analysis showed that SMW and SMW-BI were associated with activating IRS1, AKT2 and GLUT2, inhibiting FOXO1. RT-qPCR revealed that SMW and SMW-BI could increase levels of Irs1, Akt2, and Glut2 in the liver of T2DM mice and lower the level of FOXO1. Furthermore, immunofluorescence analysis showed that FOXO1 expression in the livers of T2DM mice decreased after oral administration of SMW and SMW-BI. Furthermore, molecular docking showed that SMW-BI could bind directly to IRS1 and AKT2. Conclusion: SMW and SMW-BI are potential hypoglycemic drugs and alleviate T2DM by regulating IRS1/AKT2/FOXO1 signaling. Our study provides a research idea for screening the bioactive ingredients in traditional Chinese medicine.